An assessment of supply chain performance based on the SCOR model - Claudie Tiofannya; Yogi Rahman Feriza Ginting; Atika Rahmi; Iventura Fitra Uli Tamba; Dewi Rafiah Pakpahan (Lembaga Riset, Publikasi dan Konsultasi JONHARIONO, 2026)
Supply chain management plays a strategic role in improving efficiency and competitiveness across various business and management sectors. However, differences in operational characteristics often lead to recurring challenges in supply chain performance. This study aims to analyze and synthesize supply chain performance issues and strategic challenges using the Supply Chain Operations Reference (SCOR) model. A qualitative approach with a literature review method was employed by analyzing nine scientific journal articles that examine SCOR-based supply chain performance measurement across different industries. Data were analyzed descriptively and comparatively based on SCOR performance attributes, including reliability, responsiveness, agility, cost, and asset management efficiency. The results reveal that despite differences in overall performance levels, companies face similar issues, particularly imbalances among SCOR attributes, weak responsiveness and adaptability, inefficient asset management, and limited data integration. These findings indicate that strong performance in certain attributes does not guarantee balanced supply chain performance. Therefore, structured and continuous SCOR-based performance measurement integrated into managerial decision-making is essential to support sustainable supply chain improvement